Reference Group and Testimony as determinant on Interest of Buying Exploration Nmax Motorcycle - Hary Firmansyah; Gian Riksa Wibawa; Depy Muhamad Pauzy (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This purpose’s research to determine the influence of reference group and testimonial on interest of buying exploration both partially and simultaneously toward Nmax motorcycle users in Tasikmalaya City. Design/Methodology/Approach – This research used a purposive sampling size of 100 people from Nmax motorcycle users in Tasikmalaya City as the unit of analysis. Findings – The results of these research conclude that variable of reference group and testimony partially and simultaneously have a significant effect on intereset of buying exploration among Nmax motorcycle users in Tasikmalaya City. Conclusions and Implications - Reference Groups and Testimonials have a significant positive effect on Purchase Exploration Interest among Nmax motorbike users in Tasikmalaya City. For Nmax motorbike sellers in Tasikmalaya, they can increase the Reference Group and Testimonials to increase consumer interest in buying Nmax products.